Successful Treatment of Mycobacterium caprae Infection in Two UK Cats - Emily Clark; Danielle Gunn‐Moore; Conor O'Halloran (Veterinary Medicine and Science, 2026)
ABSTRACT A 4‐year‐old, male‐neutered Savannah cat (Case 1) and a 3‐year‐old female‐neutered British shorthair cat (Case 2) were each investigated for chronic coughing, lethargy and weight loss. Thoracic imaging revealed diffuse broncho‐interstitial changes and multifocal soft‐tissue nodules (Case 1), and two cavitating masses in the left lung (Case 2). Bronchoalveolar lavage cytology (BAL) in both cases identified macrophagic inflammation with acid‐fast bacilli and was culture (Case 1) or PCR (Case 2) positive for Mycobacterium caprae . The cats were treated with 11 months (Case 1) and 9 months (Case 2) of triple antimicrobial therapy comprising pradofloxacin (5 mg/kg orally once every 24 h), rifampicin (10 mg/kg orally once every 24 h) and azithromycin (15 mg/kg orally once every 24 h). Both made complete clinical recoveries and radiographic improvement in the thoracic changes were static for 2 months prior to cessation of therapy. Both cats remain clinically well 12 and 10 months after cessation of treatment, respectively.